TEACHING VOCABULARIES IN PRIMARY EDUCATION - Abduvoxidova Feruza Yo‘lchi qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article analyzes effective methods for developing vocabulary in teaching English in primary education. Vocabulary is a key element of language learning, which plays an important role in the development of all types of speech activity of students. The main goal of the study is to identify modern, interactive and learner-centered methods for teaching new words to young students. The research used a qualitative analysis method, and scientific sources and practical experiences were studied. The results showed that games, visual aids, songs and context-based teaching methods help students learn words quickly and effectively. Also, the processes of repetition and reinforcement play an important role. In conclusion, the use of innovative and interactive approaches to teaching vocabulary in primary education significantly increases the effectiveness of education.